2011
DOI: 10.1177/0040517510395999
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of puncture behaviors of woven fabrics from finite element analyses and experimental tests

Abstract: This paper reports the puncture behaviors of woven fabrics from experimental and finite element analyses (FEAs) approaches. In the experimental approach, the puncture behaviors of three kinds of woven fabrics, plain woven, 2/2 twill woven, and 2/1 twill, were tested under quasi-static conditions and the puncture load-displacement curves of the fabrics were obtained. The puncture damage morphologies were also observed. In FEA simulation, the puncture damage evolutions were calculated at the microstructure level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…The restrained force on the yarns dramatically rises until some yarns are broken. 13,14 In our case, pristine material underwent typical puncture mechanisms, such as yarn pull-out and fabric windowing, leading not always to significant yarns fractures but merely to their separation, which allowed penetrator passage. 15 After the test, the fabric appeared to be pierced with slightly spilled fibers, but without evident signs of broken yarns.…”
Section: Resultsmentioning
confidence: 74%
“…The restrained force on the yarns dramatically rises until some yarns are broken. 13,14 In our case, pristine material underwent typical puncture mechanisms, such as yarn pull-out and fabric windowing, leading not always to significant yarns fractures but merely to their separation, which allowed penetrator passage. 15 After the test, the fabric appeared to be pierced with slightly spilled fibers, but without evident signs of broken yarns.…”
Section: Resultsmentioning
confidence: 74%
“…However, the resistance to needle puncture is much more complex, and requires careful consideration of the tightness of the fabric and the sharp profile of the needle. The puncture behavior of woven fabrics was investigated by Sun et al 93 It was observed that in the initial stage, when a sharp object contacts a woven fabric, the warp and weft crimped yarns gradually straighten and are held under tension. The stress developed in the straightened yarns is transferred to the neighboring yarns due to the integrity of the woven structure.…”
Section: Puncturingmentioning
confidence: 99%
“…Recently, several studies have been done to evaluate and improve the stab and puncture resistance of woven fabrics used for ballistic protection. 63,84,89,99,100 For example, the puncture behavior of woven fabrics was investigated from experimental and finite elemental analysis approaches by Sun et al 93 Three types (plain, 2/2 twill, and 2/1 twill) were tested under quasi-static conditions, and the load-displacement curves were plotted. Good agreement between the simulated and experimental results was obtained.…”
Section: Textile Solutionsmentioning
confidence: 99%
“…In addition, many researchers [3][4][5][6][7][8][9][10][11] relate their studies with the effect of friction by using various methods such as quasi-static test, puncture resistance test, yarn pull-out test, and through modeling (LS-DYNA). A recent study by Sun et al [12] reported the puncture behavior of woven fabric in plain, 2/2 twill, and 2/1 twill using finite element analysis (FEA).…”
Section: Introductionmentioning
confidence: 99%